A Gentle Occupation Dutch Military Operations in Iraq, 2003-2005 - ten Cate, Arthur (Leiden University Press, 2014)
A Gentle Occupation analyses Dutch military operations in the aftermath of the 2003 US-led invasion in Iraq. It raises the question why, in contrast to most allied troops elsewhere in Iraq, Dutch forces in Al Muthanna province met with little resistance and left Iraq self-confident of their ability to deal with this type of stabilisation operations